To analyze the student's solution:
- The original equation is \( \frac{1}{4}(8 - 12x) = x - 2(2x + 1) \).
- When simplified, we have \( 2 - 3x = x - 4x + 2 \), which simplifies to \( 2 - 3x = -3x + 2 \).
- The steps continue to show that \( 2 - 3x + 3x = -3x + 3x + 2 \), resulting in \( 2 = 2 \).
Since the final equation \( 2 = 2 \) is always true and is an identity, this means the original equation has infinitely many solutions. The student correctly simplified the equation, leading to this true statement.
Therefore, we can complete the statement as follows:
The student solved the equation correctly because the original equation has infinitely many solutions.